A Cancer Theory: The Central Nervous System’s Adaptive Changes Make Chronic Diseases Incurable - Jianqing, Wu; Ping, Zha (Journal of Colon And Rectal Cancer, 2022)
We examined special roles of the Central Nervous System (CNS) in an attempt to resolve the puzzle that chronic diseases cannot be cured in medicine. By exploring a skill-learning model, we found that the CNS is able to remember certain information reflecting biochemical and cellular (B&C) processes in the body. From the skill-using ability, we found that the CNS is able to control basic B&C processes that drive and power the skill. From the ability to adjust forces and moving direction of body parts, we infer that the CNS is able to adjust B&C processes that control physical acts. From this controlling capability, we inferred that the CNS must also store certain information on the baseline B&C processes, is able to up-regulate or down-regulate the B&C processes, and make comparisons in performing its regulatory functions. We found that chronic diseases are the results of deviated baseline B&C processes, the CNS plays a role in maintaining deviated baseline B&C processes, and protects the body state of a fully developed disease. The three CNS roles can explain that cancer progresses with increasing malignancy, cancer quickly returns after a surgery, cancer cells repopulate after chemotherapy and radiotherapy, cancer patients develop drug resistance inevitably, immune cells rebound after suppression, etc. We further showed that long-term exercises generally can correct part of the departures in B&C processes and thus help to reverse chronic diseases. Finally, we propose strategies for resetting the CNS’ state memory as an essential condition for curing chronic diseases and cancer.
Keywords: Cancer theory; CNS central nervous system; lost anti tumor immunity; exercise skills; incurable diseases; failure of medicine